Did the English strategy reduce inequalities in health? A difference-in-difference analysis comparing England with three other European countries - Yannan Hu; Frank J. van Lenthe; Ken Judge; Eero Lahelma; Giuseppe Costa; Rianne de Gelder; Johan P. Mackenbach (BMC, 2016)
Abstract Background Between 1997 and 2010, the English government pursued an ambitious programme to reduce health inequalities, the explicit and sustained commitment of which was historically and internationally unique. Previous evaluations have produced mixed results. None of these evaluations have, however, compared the trends in health inequalities within England with those in other European countries. We carried out an innovative analysis to assess whether changes in trends in health inequalities observed in England after the implementation of its programme, have been more favourable than those in other countries without such a programme. Methods Data were obtained from nationally representative surveys carried out in England, Finland, the Netherlands and Italy for years around 1990, 2000 and 2010. A modified difference-in-difference approach was used to assess whether trends in health inequalities in 2000-2010 were more favourable as compared to the period 1990-2000 in England, and the changes in trends in inequalities after 2000 in England were then compared to those in the three comparison countries. Health outcomes were self-assessed health, long-standing health problems, smoking status and obesity. Education was used as indicator of socioeconomic position. Results After the implementation of the English strategy, more favourable trends in some health indicators were observed among low-educated people, but trends in health inequalities in 2000-2010 in England were not more favourable than those observed in the period 1990-2000. For most health indicators, changes in trends of health inequalities after 2000 in England were also not significantly different from those seen in the other countries. Conclusions In this rigorous analysis comparing trends in health inequalities in England both over time and between countries, we could not detect a favourable effect of the English strategy. Our analysis illustrates the usefulness of a modified difference-in-difference approach for assessing the impact of policies on population-level health inequalities.